Olivera Mladenović and Folk Dances in the Context of Serbian Ethnology - Rašić (Serbia), Miloš (Bulletin of the Institute of Ethnography SASA, 2018)
Olivera Mladenović was born in 1914 in Skopje (Macedonia), but her entire professional and private life was connected to Belgrade and Serbia. Olivera Mladenović received her BA both in Yugoslav Literature and Serbian Language with the Old Church Slavonic Language, and in Ethnological Studies, while also receiving a PhD in the latter in 1965, because she considered that ethnology was important for further study of folk dances. The main subject of research by this scientist was folk dances, as she terminologically defined the subject of her study. Olivera considered folk dances from a scientific point of view, but she also practically contributed to the preservation and promotion of this phenomenon, organizing various seminars, holding lectures, participating in folklore festivals and, finally, establishing National Folk Dance and Song Ensemble of Serbia "Kolo". In this paper, using primarily archival sources and then accessible literature, I will show how Olivera Mladenović contributed to Serbian ethnology as a scientific discipline by researching folk dances. Key words: Olivera Mladenović, biography, folk dances, ethnology, ethnochoreology